Pre-quit nicotine decreases nicotine self-administration and attenuates cue- and drug-induced reinstatement. (March 2019) - Clemens, Kelly J; Stuart, Angela; Ferguson, Stuart G
Background: Administration of smoking cessation medications in anticipation of a nominated quit date can promote abstinence. How this occurs is not widely understood, but may be due to the disruption of contingencies between smoking behaviour and acute drug effects. Aims: The aim of this study was to explore this relationship, we examined the effect of pre-quit nicotine replacement therapy on susceptibility to relapse in an animal model of nicotine dependence. Methods: Rats were trained to intravenously self-administer nicotine across 20 days. Continuous low-dose nicotine was administered via a mini-osmotic pump either across the last 7 days of self-administration and across 6 days of extinction, or across extinction only. Cue- and drug-induced reinstatements of responding were then measured with mini-pumps retained, the day after mini-pump removal or one week later. Results: Pre-quit nicotine administration markedly reduced self-administration across the last days of training as the response, and its associated cues, no longer reliably predicted an acute drug effect. Pre-quit, but not post-quit, nicotine administration significantly attenuated cue-induced reinstatement once mini-pumps were removed, indicating that the contingency disruption across training reduced the conditioned reinforcing properties of the cue at test. Both pre-quit and post-quit nicotine attenuated nicotine-primed reinstatement. Conclusions: Together these results suggest that administration of a nicotine replacement prior to a nominated quit date may enhance resistance to relapse via disruption of the contingency between a response, its associated cues, and a rewarding nicotine effect.